ANALISIS ALGORITMA BLOCPLAN TERHADAP EFISIENSI KERJA PEGAWAI UIN SUNAN AMPEL SURABAYA - Zainiyah, Lilik (el-Qist : Journal of Islamic Economics and Business (JIEB), 2016)
UIN Sunan Ampel Surabaya is the education institute with area 8 ha. The condition UIN Sunan Ampel today is new builds the contruction for facility the new students, but UIN SunanAmpel have a problem on planning the building because they haven’t planning on layout for administration spaces based on theory to purpose efficients. In this research use the sampel Rektorat, Fakultas Tarbiyah dan Keguruan, Fakultas Dakwah dan Komunikasi, dan Fakultas Ekonomi dan Bisnis Islam dan Fakultas Ilmu Sosial dan Ilmu Politik. The purpose on this research is to explain how the layout condition administration spaces UIN SunanAmpel, how efficient analysis on the work of employee, and how the plan layout in administration spaces if use the softwareBlocplan. Central data the softwareneeds are Activity Relation Chart (ARC), and wide area work station needed. This Research use the kualitatif description. The Procedur of collect data is survei on pra research, study on literature, study on field like interview, observation, dan documentation. The result this research is condition of UIN SunanAmpelefficient not yet based on analysis ofgood office layout principle and Blocplan analysis, except FakultasDakwahdanKomunikasi. Blocplan analysis will get 20 layout for opsi and can choosed the best layout for each sampel. The best layout will be have the good on wide of space and best on the relation activity and the reason relation for efficient and organize the same works. Based on the analysis, one of the opinion is apply layout on the recommendation, because UIN SunanAmpel have a layout less efficient if we talk about work employee.